“Second-Chance” Education: Redefining Youth Development in Grenada - Perez Gonzalez, Laura (Postcolonial Directions in Education, 2020)
With the end of the Grenada Revolution and the subsequent American invasion, the nation’s education policies shifted from being conceptualised as a national development strategy “fashioned in our own image”, to being a project aiming to strengthen the region’s global marketplace participation through the creation of the “ideal Caribbean person/citizen/worker”. Recognising the discursive shifts in education and development, this article focuses on how Grenadian youth (16-24) interpret these institutional objectives through their participation in “second-chance” education, or nonformal education. Following Henri Lefebvre’s (1991) spatial triad, the analysis examines the concept of "second-chance" education as a socially produced space conceived by the state, perceived by organisations, and lived by the students. The article reveals gaps between discourse and practices of youth in development, highlighting ways in which youth actively navigate and respond to the socioeconomic and geographic realities involved with “second-chance” education organisations, national growth, and regional integration.
Keywords: Second-chance education; youth development; sociospatial analysis; CARICOM; Grenada